Introduction to Classical Control Theory - Zhou Gaofeng; Zhang Qi (Modern Control Systems: Theory, Design and Applications, 2025)
In this chapter, some highlights in classical control theory was narrated or explained. Specific contents were also introduced, which include: system representation, feedback, performance measurement and analytic methods of classical control theory.